PERSEPSI, SIKAP, DAN STRATEGI KOPING KELUARGA MISKIN TERKAIT PROGRAM KONVERSI MINYAK TANAH KE LPG DI KOTA BOGOR - Latifah, Eka Wulida; Hartoyo, Hartoyo; Guhardja, Suprihatin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2010)
Nowadays, the increasing of energy demand is related to the growth of economy activities and the growth of population. The increasing of Indonesian population over years and the increasing of variaty of economy activities and its output within society causing increasing demand of energy being something that cannot be avoided. In addition, Indonesia’s dependable to energy had increased the demand of energy. Meanwhile, energy reserve is running low both in Indonesia and the world. Energy crisis that happen this time trigger various side to do new experiments especially that concern to public policy. One of the step strived by the government to overcome this kerosene crisis is the conversion from kerosene to LPG. The conversion from Kerosene to LPG program is one of the efforts that done by government to decrease dependency society towards kerosene. The aim of this study was to analyze of the poor family respons to cerosene convertion program to LPG in Sindang Barang Village and Cikaret Village, Bogor City. The Study implemented cross sectional and survey method through the process of purposive sampling procedures. One of the criteria of the study location was the location that had the highest quantity which received cerosene convertion program to LPG. The samples of the family were chosen randomly from the chosen location. The total of samples was 60 families. The study used descriptive analysis that contains of secondary data, literature study, and primary data (from questionnaire). Beside that, Pearson correlation dan linear regression was used to analyze data. The result found out that 18,33% of the samples were actually not really receive the program. Around 60% of the family had monthly expense per capita of Rp 222.123,00 which was below the poverty line. Kerosene conversion program is proved to decrease family expenditure at kerosene user who converts to LPG user. This is showed by expenditure depreciation existence after conversion program is carried out around Rp 66.400,00 every month (used kerosene prices before program) and Rp 202.350,00 every month (used kerosene prices after program). But for samples that convert from to LPG, the expenditure rise from Rp 10.250,00 every month become Rp 44.700,00 every month.The study also found that in general, most of LPG user ask money to the extended family and cook in their family when they havenot money to buy LPG refill. The Government wished can give the sosialization a good way to use LPG, not only give the information that LPG is safe, clean, cheap, and good for environment. Besides that, its need to empower society in order to prepare money to buy LPG refill.